Effects of the Hospital Gradation System on Patient Behavior and Satisfaction: An Investigation of Dental Health Care - Wen-Jen Chang; Yen-Hsiang Chang; Hsu-Chuan Hsiao (Tehran University of Medical Sciences, 2015)
No Abstract